ESTUDIO DE FACTIBILIDAD PARA LA CRIANZA DE CERDOS Y LA COMERCIALIZACION DE CARNE EN LA COMUNIDAD DE SASAPAS DEL CANTON GUALAQUIZA, PROVINCIA DE MORONA SANTIAGO. - ORELLANA AREVALO, JOSE FABIAN (2019)
The main objective of this research project is to determine the feasibility of the investment proposal regarding the implementation of a meat production and marketing company in the Gualaquiza canton of Morona Santiago. For the development of this project it was essential to develop four objectives, which address the feasibility of the market study, in which the conditions of supply, demand and suppliers are established; the feasibility of the technical study is essential to know the size, location, engineering of the project and the organizational design; the financial study, the investment, financing, cost, income and equilibrium point of the production are announced and finally in the financial evaluation, which through its indicators was determined the feasibility of the investment proposal. To carry out the research it was necessary to use certain materials and methods, which allowed the collection and analysis of relevant data for its development. In the results obtained from the market study it was determined that there is an unsatisfied demand for the first year of 26,000 pounds per year. The commercialization will be carried out directly: company - consumer. Therefore, within the technical study the company in the canton Gualaquiza develops its activities with an installed capacity of 83200 pounds per year and a used capacity of 26000 pounds for the first year since the facilities of the shed will work at 40%, from of the second year he will work at 100% having a utilized capacity of 83200 pounds. The constitution of the company will be under the regime of Limited Company, it will count on the personnel in agreement with the hierarchic levels and the necessary dependencies for the development of the activities of the company, for it the design of the organizational charts was made: structural, positional and functional. Regarding the financial study it was found that the investment is $ 58,017.59; that 48% will be financed by the partners of the company and 52% by the Ban Ecuador financial entity, which represents the amount of $30000. Analyzing the total production costs, it has been concluded that the price of the product will be $ 1.88 cents per pound. The financial evaluation determined: the 5 Net Present Value is of $ 21094.46; the Internal Rate of return is 13.50%, in the Benefit Cost Ratio the profit will be 0.52 cents; The Capital Recovery Period is 3 years 5 months and 12 days, the Sensitivity Analysis with increase in costs, is 15.45%. After to see applied the financial evaluation indicators that allow to evaluate the feasibility of the project to accept or not the investment; the case is presented that this study yields positive results, so it is recommended to put into practice and invest in the project.